Analisis Keharmonisan Rumah Tangga Berdasarkan Tingkat Pendidikan Suami Istri - Badi’, Ahmad; Munawar, Khoeri (Indonesian Journal of Humanities and Social Sciences, 2023)
This study aims to analyze household harmony in husbands and wives who have different levels of formal education. This research uses descriptive qualitative research with a type of field research, using data collection techniques through observation, interviews and documentation. Based on the research that the level of education on household harmony, both formal and informal education levels experienced by married couples in Mondo Village, has their household harmony because education can foster how good religion, maturity in acting and thinking, have leadership, manners, responsibility, and improve the economy so that a harmonious household is formed.